Antibiotic therapy for Klebsiella pneumoniae bacteremia: Implications of production of extended-spectrum beta-lactamases - DURMUŞOĞLU, LÜTFİYE (OXFORD UNIV PRESS INC, 2004)
The prevalence of extended-spectrum beta-lactamase (ESBL) production by Klebsiella pneumonia approaches 50% in some countries, with particularly high rates in eastern Europe and Latin America. No randomized trials have ever been performed on treatment of bacteremia due to ESBL-producing organisms; existing data comes only from retrospective, single-institution studies. In a prospective study of 455 consecutive episodes of Klebsiella pneumoniae bacteremia in 12 hospitals in 7 countries, 85 episodes were due to an ESBL-producing organism. Failure to use an antibiotic active against ESBL-producing K. pneumoniae was associated with extremely high mortality. Use of a carbapenem ( primarily imipenem) was associated with a significantly lower 14-day mortality than was use of other antibiotics active in vitro. Multivariate analysis including other predictors of mortality showed that use of a carbapenem during the 5-day period after onset of bacteremia due to an ESBL-producing organism was independently associated with lower mortality. Antibiotic choice is particularly important in seriously ill patients with infections due to ESBL-producing K. pneumoniae.
Keywords: ESCHERICHIA-COLI; PIPERACILLIN-TAZOBACTAM; CLINICAL-FEATURES; IN-VITRO; RESISTANCE; EPIDEMIOLOGY; OUTBREAK; PREVALENCE; CEFEPIME; SHV-5